Efficiency of use of alternative substrates in the production of papaya seedlings (Research, Society and Development, 2020)
In the formation of papaya seedlings (Carica papaya L.) the combination of the ideal substrate to obtain quality seedlings is essential. Thus, it was evaluated the influence of the decomposed stem of babassu (CDB), carbonized rice straw (PAC) and soil (S) in the formation of papaya seedlings. An experiment was carried out in a greenhouse in a completely randomized design with 12 treatments (substrates) and 4 replications, being: T1 - 0% PAC + 60% CDB + 40% S; T2 - 10% PAC + 50% CDB + 40% S; T3 - 20% PAC + 40% CDB + 40% S; T4 - 30% PAC + 30% CDB + 40% S; T5 - 40% PAC + 20% CDB + 40% S; T6 - 50% PAC + 10% CDB + 40% S; T7 - 0% PAC + 100% CDB; T8 - 20% PAC + 80% CDB; T9 - 40% PAC + 60% CDB; T10 - 60% PAC + 40% CDB; T11 - 80% PAC + 20% CBD and T12 - 100% PAC. The results were submitted to analysis of variance by the “F” test and the means compared by the Duncan test. With the exception of the emergence speed index, the results differed statistically for the leaf area, plant height, stem diameter, root length, root volume, fresh mass of the aerial part and root system, dry mass of the aerial part and root system and Dickson's quality index, obtaining greater efficiency with the T5 substrate followed by T6. The results indicated the viability of using carbonized rice straw and decomposed babassu stem in the formation of papaya seedlings.